Indigenous Knowledge Bali Aga dalam Gringsing Motif Lubeng: Ritus Sakral dan Pemertahanan Identitas di Tenganan Pegringsingan - I Nengah Juliawan (Kamaya: Jurnal Ilmu Agama, 2025)
The phenomenon of the erosion of the younger generation's understanding of the indigenous knowledge of the Gringsing Lubeng motif among Tenganan Pegringsingan people is the central issue of this research, driven by globalization and the economic shift to tourism, which threatens the transmission of knowledge. This study aims to uncover how indigenous knowledge in the Lubeng motif functions as a tool for identity preservation and to analyze the Tenganan community's adaptation strategies in responding to the challenges of modernity. This study uses qualitative methods with an ethnographic approach to uncover the emic perspective through participant observation, in-depth interviews, and focus group discussions (FGDs). Data were analyzed using the Miles & Huberman model and Spradley's ethnographic analysis. The results show that the indigenous knowledge of Gringsing Lubeng is a living knowledge system manifested in three domains: the sacred materiality of Tridatu, double ikat technology as embodied knowledge, and the symbolism of the Lubeng motif as a wearable cosmogram. This motif maps the Bali Aga cosmology, where the Tapak Dara symbol represents the fundamental values ​​of Tri Hita Karana, and the scorpion serves as an apotropaic symbol (a deterrent to disaster). This knowledge serves as material agency in lifecycle and communal rituals. It is concluded that the indigenous knowledge of Gringsing Lubeng functions as a holistic identity defense system. The community's layered adaptation strategies, including upholding customary rules (awig-awig), everyday resistance through slow production, and a cultural firewall strategy by intelligently creating commercial products (Idup Anak), successfully protect the sacredness of core heritage amidst the pressures of commercialization.